Taḥlīlu al Binyawiyati fī al Ghinā’i “Nasamāt al Hawak li Mevlān Kurtīsyi (al Tarkību al Ẓāhiriyatu wa al Bāṭiniyyatu) - Karnaini, Zul; Buska, Wahyudi (Al-Uslub: Journal of Arabic Linguistic and Literature, 2022)
Abstract:Literature is an expression of one`s feelings that contains beauty and meaningful mesenges. Song lyrics are still part of literature because they are sung poerty. One of the song lyrics that contains beauty and meaning is found in the song “Nasamatu Hawak” by Mevlan Kurtishi. This research was conducted because the researcher found problems with the song “Nasamatu Hawak” by Mevlan Kurtishi: firsh what is the physical structure of the song “Nasamatu Hawak” by Mevlan Kurtishi, second what is the inner structure of the song “Nasamatu Hawak” by Mevlan Kurtishi. The purpose of this study is to describe the physical and mental structure in the song “Nasamatu Hawak” by Mevlan Kurtishi.The type of research used is qualitative research. The data is this study are the lyrics of the song “Nasamatu Hawak” by Mevlan Kurtishi. The research data source is the song “Nasamatu Hawak” by Mevlan Kurtishi. Data collection methods and techniques use are, (1) one speech, (2) identifying the data based on speech, (3) giving meaning and (4) describing the research data. The results show that there are a number of physical and mental structures in the song “Nasamatu Hawak” by Mevlan Kurtishi: 1. Physical structure (face, diction, imagination, concrete words, figurative language, and ryhmes), 2. Inner structure (theme, sense of, tone, and messenge)